UZBEK CHILDREN'S LITERATURE (World Bulletin of Social Sciences, 2023)
A collection of literary, artistic, scientific, popular, and public works written for children and adolescents is known as children's literature. This is mostly made up of fiction. The world's children's literature, including that of the Uzbek people, starts with examples of oral creativity, the majority of which are intended for young children. These include quick sayings, riddles, play songs, narrations, legends, fairy tales, proberb's, parables, and epics. In this article, opinions and reflections on Uzbek children's literature will be discussed